2022
DOI: 10.3389/fsoc.2022.856613
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Conflict Among Higher Education Institution Workers' During COVID-19: A Demands-Resources Approach

Abstract: Higher Education Institutions' (HEI) workers were highly impacted by the COVID-19 pandemic, which magnified gender differences in terms of management of work and personal life. Most studies published so far have primarily focused on a group of HEI workers' (i.e., teachers and researchers), but not on staff members, despite their crucial role for HEI functioning. Following the Job Demands-Resources theory, we aimed to: (i) characterize work-life conflict (WLC) among men and women workers from an HEI (staff and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…Previous studies concluded that females in HE suffered an increased workload and that managing work–life balance was challenging compared to males (Obianuju and Gamede, 2021; Garraio et al. , 2022; Newlin and Anthony, 2022).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies concluded that females in HE suffered an increased workload and that managing work–life balance was challenging compared to males (Obianuju and Gamede, 2021; Garraio et al. , 2022; Newlin and Anthony, 2022).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…, 2021; Romeo et al. , 2021; Obianuju and Gamede, 2021; Garraio et al. , 2022; Newlin and Anthony, 2022).…”
Section: Literature Review – Insights and Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nyilván most én oktatóként tudok erről beszélni, de ha a családbarát irányból közelítem meg a kérdést, akkor a rugalmasság az, ami nagyon fontos, és ez az oktatóknál jobban biztosítható." Ez egybecseng Garraio et al (2022) megállapításával, mely szerint a munka-magánélet egyensúlya az oktatók és a kutatók esetén jobban megvalósul, szemben a nem oktató munkatársakkal.…”
Section: Családunclassified
“…Academics' varying responses to changing working conditions can potentially be explained by the job demands and resources they experience during the pandemic. Several quantitative studies have provided valuable insights into academics' experiences of job demands and resources during the pandemic (Kulikowski et al, 2021 ; Mäkiniemi et al, 2021 ; Wood et al, 2021 ; Garraio et al, 2022 ; Ghislieri et al, 2022 ; Taylor and Frechette, 2022 ). However, to the best of our knowledge, there is a lack of qualitative studies in this area (Naidoo-Chetty and du Plessis, 2021a ).…”
Section: Introductionmentioning
confidence: 99%